The Role of Property Tax in Municipal Budget - Eva Tomášková; Michal Radvan (Institutiones Administrationis)
Tax revenues of municipalities can be divided into shared and entrusted (own, local) taxes in the Czech Republic. There are several local taxes sensu lato, the most important of which is the immovable property tax. This article is set to evaluate its role in the Czech municipal budgets, predominantly by way of comparing the economic data concerning the revenues of local self-government units in OECD countries. From a legal perspective, the text describes and critically analyzes the legal regulation of the Czech immovable property tax and specifically points out municipalities’ potential to influence their revenue with regard to political debates and recent changes in legal regulation. In the discussion part, the challenges connected with the changes in the legal regulation of the immovable property tax and changes in the budget determination of taxes are defined, and the impacts of these changes are analyzed in details. The authors argue that the role of the property tax is negligible and municipalities must rely on sources of funding other than local taxes to meet their statutory obligations.